The Impact of Organizational Capabilities, Green Absorptive Capacity, and Strategically Environmental Orientation on Sustainable Competitive Advantage Through Green Innovation in SMEs in Jambi Indonesia - Eddy Suratno; Johni Paul Karolus Pasaribu; Mahda Auliannisya; Raditya Dwi Saputra; Nelsa Prabatiwi Sukmana (Majapahit Journal of Islamic Finance and Management, 2025)
This study investigates the effects of organizational capabilities, green absorptive capacity, and strategic environmental orientation on sustainable competitive advantage through green innovation in SMEs in Jambi, Indonesia. A quantitative approach was utilized, employing a structured survey distributed to 300 SME managers in Jambi and Sungai Penuh. The data collected was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS software to assess the relationships between variables and test the proposed hypotheses. The findings show that organizational capabilities, green absorptive capacity, and strategic environmental orientation significantly influence green innovation in SMEs. Moreover, green innovation was found to mediate the relationship between these organizational factors and sustainable competitive advantage. These results emphasize the importance of integrating internal capabilities and green practices for improving long-term business performance and competitiveness in SMEs. This study contributes to the literature by providing a comprehensive model that links organizational capabilities, green absorptive capacity, and strategic environmental orientation to green innovation, ultimately enhancing sustainable competitive advantage. The unique combination of these factors in the context of SMEs in Indonesia addresses a gap in existing research on eco-innovation and sustainable performance. The study offers practical implications for SME managers and policymakers by highlighting the need for fostering green capabilities and supporting eco-innovation initiatives. Future research could explore the role of external environmental pressures in influencing these relationships.